2017
DOI: 10.3390/su9081482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar Application on CO2 Emissions from a Cultivated Soil under Semiarid Climate Conditions in Northwest China

Abstract: Biochar amendments to soil have potential as a climate change mitigation strategy. However, their effect on carbon exchange in different ecosystems has not been well evaluated. Understanding how biochar affects carbon exchange from agricultural soil is essential for clarifying the contribution of biochar management to the carbon budget. We performed a laboratory and a two-year field experiment to investigate the short-and medium-term effects of biochar application on CO 2 emissions from semiarid farmland. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 58 publications
5
34
1
Order By: Relevance
“…Consumption of rice contaminated with PTEs is a major pathway for human exposure to PTEs as revealed in China's so called "Cancer Villages"; hence, sewage sludge biochar was applied to suppress PTE (As, Cd, Co, Cu, Mn, Pb, and Zn) phyto-availability in soil to reduce PTE levels in rice grown in mining-impacted paddy soils [61]. Risk assessment indicated that 10% biochar (P ≤ 0.05) decreased the daily intake, associated with the consumption of rice by 68,42,55,29,43,38, and 22% PTEs, respectively [61]. Health quotient (HQ) indices for PTEs (except for As, Cu, and Mn) were <1, indicating a suppression of health risk pointing to the incremental lifetime cancer (ILTR) value for iAs (AsIII + AsV) associated with the consumption of rice significantly reducing (P ≤ 0.01) by 66% [61].…”
Section: Health Riskmentioning
confidence: 99%
“…Consumption of rice contaminated with PTEs is a major pathway for human exposure to PTEs as revealed in China's so called "Cancer Villages"; hence, sewage sludge biochar was applied to suppress PTE (As, Cd, Co, Cu, Mn, Pb, and Zn) phyto-availability in soil to reduce PTE levels in rice grown in mining-impacted paddy soils [61]. Risk assessment indicated that 10% biochar (P ≤ 0.05) decreased the daily intake, associated with the consumption of rice by 68,42,55,29,43,38, and 22% PTEs, respectively [61]. Health quotient (HQ) indices for PTEs (except for As, Cu, and Mn) were <1, indicating a suppression of health risk pointing to the incremental lifetime cancer (ILTR) value for iAs (AsIII + AsV) associated with the consumption of rice significantly reducing (P ≤ 0.01) by 66% [61].…”
Section: Health Riskmentioning
confidence: 99%
“…Switchgrass can grow in less productive soils under a broad range of environmental conditions, and requires minimal soil preparation and a relatively small amount of nitrogen (N) [8,9]. Numerous approaches have been proposed to improve switchgrass productivity while reducing environmental impacts [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar, applied as a soil amendment, has been promoted as a climate change mitigation tool as it has the potential to reduce soil greenhouse gas emissions and increase soil carbon sequestration [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For laboratory incubation studies, biochar decreases (Spokas, Koskinen, Baker, & Reicosky, 2009) or increases (Stewart, Zheng, Botte, & Cotrufo, 2013;Zheng, Stewart, & Cotrufo, 2012) CO 2 emissions. However comparisons of laboratory incubation studies and field studies show that CO 2 emission responses to biochar are consistently higher in incubation studies than in field or greenhouse studies (He et al, 2017;Shen, Zhu, Cheng, Yue, & Li, 2017). The response of exoenzymes to biochar amendments have largely been conducted in laboratory incubations with variable results (Awad, Blagodatskaya, Ok, & Kuzyakov, 2012;Bailey, Fansler, Smith, & Bolton, 2011;Demisie, Liu, & Zhang, 2014;Ouyang, Tang, Yu, & Zhang, 2014).…”
mentioning
confidence: 99%